OPTIMIZING DIGITAL LITERACY: COUNSELING ON THE USE OF SMART SOCIAL MEDIA AMONG HIGH SCHOOL STUDENTS PONPES ARSYADA BOGOR - Albar, Fauzan Manafi; Salsabil, Syifa Hanifa; Priyana, Indarta; Chrisulianti, Rizki; Jaya, Umban Adi (Jurnal Abdimas Bina Bangsa, 2024)
This counseling activity on the smart use of social media for Arsyada Bogor High School students was held on September 14, 2024. This counseling uses an educational, participatory, and evaluative approach that aims to improve digital literacy and understanding of ethics in the use of social media among students. This activity consisted of educational sessions, interactive workshops, group discussions, and awareness campaigns. Based on the evaluation results, the counseling successfully improved students' understanding of digital literacy, online privacy, and ethical use of social media. Feedback from participants showed high satisfaction with the methods and materials used. However, time constraints and varying levels of student understanding posed challenges in delivering in-depth materials. The outreach had a positive impact, but requires ongoing support and follow-up programs to ensure students continue to apply the knowledge gained in their daily use of social media.